Role of endometrial microRNAs in repeated implantation failure (mini-review) - Goharitaban, Sepide; Abedelahi, Ali; Hamdi, Kobra; Khazaei, Mozafar; Esmaeilivand, Masoumeh; Niknafs, Behrooz (Frontiers in Cell and Developmental Biology, 2022)
MicroRNAs (miRNAs) play various roles in the implantation and pregnancy process. Abnormal regulation of miRNAs leads to reproductive disorders such as repeated implantation failure (RIF). During the window of implantation, different miRNAs are released from the endometrium, which can potentially reflect the status of the endometrium for in vitro fertilization (IVF). The focus of this review is to determine whether endometrial miRNAs may be utilized as noninvasive biomarkers to predict the ability of endometrium to implant and provide live birth during IVF cycles. The levels of certain miRNAs in the endometrium have been linked to implantation potential and pregnancy outcomes in previous studies. Endometrial miRNAs could be employed as non-invasive biomarkers in the assisted reproductive technology (ART) cycle to determine the optimal time for implantation. Few human studies have evaluated the association between ART outcomes and endometrial miRNAs in RIF patients. This review may pave the way for more miRNA transcriptomic studies on human endometrium and introduce a specific miRNA profile as a multivariable prediction model for choosing the optimal time in the IVF cycle.